Characteristics and numerical simulation of maize ear threshing under mixed airflow - Li, Xinping; Li, Yanan; Peng, Bin; Xu, Shendi; Wang, Junyi; Sun, Ruizhe (International Journal of Agricultural and Biological Engineering, 2025)
To make up for the gap in the research on high water content maize threshing by airflow, this study took high-speed, low flow, low-speed high flow airflow, and high water content maize ear as the research basis. The variation of air flow impacted threshing in numerical simulation, and the variation process of smoke visualization in the threshing area was compared. Taking the maize ear direction, the angle between the maize ear and the air pipe, the diameter of the air pipe, and the flow rate of the air compressor as factors, single-factor and quadratic regression orthogonal rotation combination tests were carried out, and the parameters were optimized. Finally, high-speed photography was used to shoot the maize kernels’ shelling process, and movement rules were analyzed from both the front and side views. The results showed that the velocity changes of each section under the numerical simulation are consistent with the flow state changes of smoke. The velocity reached its maximum on the circumference of the maize ear surface and presented a symmetrical distribution. Due to the velocity gradient and pressure gradient difference, the high-speed airflow would entrain the phenomena of the low-speed airflow. When the transverse maize ear, the angle between the maize and the airflow tube) was 45°, the diameter of the airflow tube was 7 mm, the flow rate of the airflow tube was 33 m/s, the loose amount was 10 pieces, the threshed amount was 15 pieces, and the damage rate was below 3%. Through high-speed photography, it was found that the cyclic force circle was destroyed after the maize kernel fell off, the motion of the removed maize kernel was similar to the oblique throwing motion, and the threshing process was carried out in the unit of “arrangement unit”. The threshing process followed the “arrangement law”, and the threshing track was “spiral”. The results of this research can provide ideas for the mechanical design and development of high-moisture-content maize threshing by air.Keywords: maize ear, impact threshing, numerical simulation, airflow, high moisture contentDOI: 10.25165/j.ijabe.20251803.9220Citation: Li X P, Li Y N, Peng B, Xu S D, Wang J Y, Sun R Z, et al. Characteristics and numerical simulation of maize ear threshing under mixed airflow. Int J Agric & Biol Eng, 2025; 18(3): 265–275.